Implementation of Active Learning Methods for Fiqh Subjects in the Independent Curriculum at MI Al-Fachran Tanjung Anom - Ardilla, Tasya; Abrianto, Danny (Universitas Pahlawan Tuanku Tambusai, 2025)
Education is an effort to increase one's potential, both physically and spiritually, which refers to the process of changing one's attitudes and behavior. The learning process is part of the stages of increasing one's potential, where this process involves various activities including reciprocal communication, exploration, and creativity. This study discusses the implementation of the learning process using active learning methods in the subject of Islamic jurisprudence for students at MI Al-Fachran Tanjung Anom. The purpose of this implementation is to improve learning abilities and develop students' thinking in solving a problem. The method used in this study is qualitative, including field observations and interviews, which will then be presented in the form of data so that researchers can determine and draw conclusions. From the results of the study, it was found that this active learning method is a very effective step to take in the teaching and learning process. This statement was confirmed by several sources consisting of several educators and students who were the objects of this study.